Les premières années de la diplomatie états-unienne : l’influence décisive de Benjamin Franklin à Paris (1776-1778) - Christian Lerat (Transatlantica)
This paper relies on scholarship produced over the last decades to take stock of the role of Benjamin Franklin as founding father of American diplomacy. Focusing on the first part of Franklin’s mission to France–which leads us to the signing of the treaties of amity and commerce and of political alliance with France (February 6, 1778), enables one to assess how Franklin soon succeeded in meeting the challenges he was confronted with and also in showing flexibility in his reactions to French expectations. His main asset certainly lay in his being able to capitalize on what the other American emissaries were so cruelly deprived of, to the point of becoming the latter’s rival. Blending personal charm with an inborn talent for communication and… manipulation, Franklin easily managed recognition as the main negotiating partner of a Court whose understandable reticence he knew how to overcome, eventually making France the ally of a young republic—a landmark the importance of which was to prove decisive.